18F-FDG PET/CT scanning: Biological effects on patients: Entrance surface dose, DNA damage, and chromosome aberrations in lymphocytes - Prasad, Akshaya; Visweswaran, Shangamithra; Kanagaraj, Karthik; Raavi, Venkateswarlu; Arunan, M.; Venkatachalapathy, E.; Paneerselvam, S.; Jose, M.T.; Ozhimuthu, Annalakshmi; Perumal, Venkatachalam (Mutation research. Genetic toxicology and environmental mutagenesis, 2019)
•Effective dose ranges between 4.01–6.6 and 16.40–72.1 mSv for PET & CT respectively.•The order of measured ESD to various regions is pelvis > shoulder > head.•DNA damage was measured using γ-H2AX, p53Ser−15, CA and MN markers.•The γ-H2AX, p53Ser−15 and MN did not show increase (p > 0.05) in post-scanning.•CA showed a significant increase (p < 0.05) in post-scanning compared to pre-scanning. Positron Emission Tomography/Computed Tomography (PET/CT), a combination of PET and CT, is used in tumor staging, therapy planning, and treatment response monitoring. During PET imaging, patients receive low doses of radiation, which can induce an adaptive response and necessitate higher doses for therapeutic efficacy. Higher doses may augment toxicity to normal cells. We are examining the effects of short-term, low-dose exposures to ionizing radiation. Entrance Surface Dose (ESD) to head, shoulders, and pelvis regions were measured using Li2B4O7: Mn thermoluminescent dosimeters. Induced DNA damage in lymphocytes was measured using γ-H2AX, p53Ser−15, chromosome aberrations, and micronucleus formation in subjects (n = 25) who underwent 18F-FDG PET/CT. The mean ESD ± SD value obtained were 32.40 ± 16.86, 32.58 ± 14.22, 32.02 ± 15.42, 43.55 ± 18.25 and 42.80 ± 24.67 mGy for the head, right shoulder, left shoulder, right pelvic, and left pelvic regions, respectively. The effective doses of PET and CT ranged from 4.01 to 6.61 and 16.40–72.18 mSv, respectively, and the obtained Dose Length Product (DLP) varied from 1093 to 4812 mGy*cm. There was no correlation between DLP and ESD (r2 = 0.1). The chromosome aberration assay showed a significant increase (p < 0.05), post-scanning vs. pre-scanning; the γ-H2AX, p53Ser−15, and micronucleus assays did not show significant increases. Induced DNA damage showed inter-individual variation among the study subjects. Our results imply that the patients received a biologically significant dose during 18F-PET/CT scanning and precautions may be needed to reduce any long-term risk of exposure.